Effects of high stimulus frequencies on SEPs of patients with neuro-Behcet's disease - (:unkn) unknown (CANADIAN J NEUROL SCI INC, 2006)
Background: Beheet's disease is a multisystemic vascular inflammatory disorder of unknown origin. It is relatively rare and central nervous system involvement is seen in 5% of affected individuals. Somatosensory evoked potentials (SEPs) can provide information that shows the presence of clinically unsuspected lesions in the central nervous system of these patients. However, the effects of changing the stimulus frequencies on latencies of SEP potentials and central conduction time (CCT) in patients with neuro-Beheet's disease (NB) have not been studied yet. In this study, our aim was to reveal these effects to investigate whether the change of stimulus frequencies could be of convenient use in obtaining more accurate CCT estimations in SEP studies of these patients. Methods: We performed median nerve SEPs of 14 patients with NB and 15 healthy volunteers. We changed the stimulus frequency: 2 Hz, 4Hz, 6Hz and 9Hz in successive recordings and statistically compared the changes on SEP potentials and peak and onset CCT in the neuro-Beheet (NB) group and the normal group. Results: Our results indicated that the onset CCT values of the NB group were higher than the normal group at 4Hz and 9Hz stimulations. However, the comparison of peak CCT in the NB group and the normal group did not show any statistically meaningful differences at all stimulation frequencies. Conclusion: Onset CCT has not been measured before in former SEP studies of patients with NB. We highly recommend measuring onset CCT at higher stimulation frequencies in order to reveal central conduction time pathologies in these patients.
Keywords: SOMATOSENSORY-EVOKED-POTENTIALS; CENTRAL CONDUCTION TIME; NEUROLOGICAL INVOLVEMENT; PEAK METHODS; STIMULATION; ONSET